Evaluation of topographical and chemical modified TiAl6V4 implant surfaces in a weight‐bearing intramedullary femur model in rabbit. Issue 3 (12th August 2019) - Bretschneider, Henriette; Mettelsiefen, Jan; Rentsch, Claudia; Gelinsky, Michael; Link, Helmut D.; Günther, Klaus‐Peter; Lode, Anja; Hofbauer, Christine
Abstract: For cementless total joint replacement implants, the biological response to physicochemical surface characteristics is crucial for their success that depends on fixation by newly formed bone. In this study, the surface of TiAl6V4 (Tilastan®) implants was modified by (a) corundum blasting, (b) corundum blasting followed by electrochemical calcium phosphate (CaP) deposition, and (c) titanium plasma spraying followed by electrochemical CaP deposition. All modifications resulted in a surface roughness suitable to enhance primary implant stabilization and to favor osteoblast adhesion and function; the thin, biomimetic CaP coating is characterized by fast resorbability and served as chemical cue to stimulate osteogenesis. After implantation in a full weight‐bearing rabbit intramedullary distal femur model, osseointegration was investigated after 3, 6, and 12 weeks. For all modifications, new bone formation, occurring from the endosteum of the femoral cortical bone, was observed in direct contact to the implant surface after 3 weeks. At the later time points, maturation of the woven bone into lamellar bone with clearly defined osteons was visible; the remodeling process was accelerated by the CaP coating. The ingrowth of newly formed bone into the pores of the titanium plasma sprayed surfaces indicates a strong interlock and finally implant fixation. Our findings indicate a positive impact of the tested surface modifications on osseointegration.